Використання доказів як етап доказування у кримінальному провадженні - Щербаковський, М. Г.; Shcherbakovskyi, M. H.; Михайло Щербаковський (Вісник Харківського національного університету внутрішніх справ. - 2017. - № 2 (77). - С. 88-95, 2017)
Розглянуто зміст етапів доказування у кримінальному проваджені. Показано, що заключним його етапом є використання доказів, яке являє собою розумове та праксеологічне оперування доказовою або орієнтуючою інформацією з метою вирішення кримінально-правових, процесуальних, криміналістичних і кримінологічних завдань.

We distinguish from three to nine stages of proving in criminal proceedings within the special literature. The author argues that the collection, research and evaluation of evidence are initial stages of proving. Its final stage is the usage of evidence obtained during the investigation of a crime. The author has allocated four common directions of using evidence and specific objectives during the investigation of crimes that relate to them. The purpose of using evidence in criminal and legal direction is the qualification of criminal acts, setting features and elements of corpus delicti. Evidence is used in criminal and procedural direction in order to obtain new evidence, verification of other evidence, forming complexes of evidence, grounding procedural decisions. The evidence in forensic direction is used to nominate and verify leads, modeling mechanism of a crime and its components (unknown perpetrator, tools, etc.), identifying persons and objects; overcoming the counteraction to investigation; grounding tactical decisions, etc. Evidence is used in criminological direction to establish the causes and conditions that contributed to the commission of crimes. The usage of evidence in criminal proceedings is the next stage of proving after the collection, verification and evaluation of evidence, the content of which is rational (logical) and praxeological (of activity) operating of the established proving or directing information to address criminal and legal, procedural, forensic and criminological tasks.

Рассмотрено содержание этапов доказывания в уголовном производстве. Показано, что его заключительным этапом является использование доказательств, представляющее собой мыслительное и праксеологическое оперирование доказательственной или ориентирующей информацией с целью решения уголовно-правовых, процессуальных, криминалистических и криминологических задач.
Using evidence as a stage of proving in criminal proceedings
Использование доказательств как этап доказывания в уголовном производстве
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Україна. Ukraine. Украина; Наукові публікації. Scientific publications. Научные публикации; кримінальне провадження; доказування; етапи доказування; використання доказів; criminal proceedings; evidence; stages of proving; usage of evidence; уголовное производство; доказывание; этапы доказывания; использование доказательств